2017
DOI: 10.2196/jmir.6668
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Determinants and Patterns of Online Health Information Seeking: Results From a Representative German Health Survey

Abstract: BackgroundOnline health information-seeking behavior (OHISB) is currently a widespread and common behavior that has been described as an important prerequisite of empowerment and health literacy. Although demographic factors such as socioeconomic status (SES), age, and gender have been identified as important determinants of OHISB, research is limited regarding the gender-specific motivational determinants of OHISB and differences between women and men in the use of online resources for health information purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
97
4
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 59 publications
17
97
4
7
Order By: Relevance
“…Fridriksdottir et al reported in their review that web‐based interventions positively affected anxiety, depression, and HRQoL for cancer patients who mostly were breast or female cancer survivors . Previous studies have indicated that website attributes, Internet usage patterns, and habits are different across genders . The differences in the findings of our review and those from the other reviews suggest that the effects of TBIs may also vary by gender.…”
Section: Discussioncontrasting
confidence: 49%
“…Fridriksdottir et al reported in their review that web‐based interventions positively affected anxiety, depression, and HRQoL for cancer patients who mostly were breast or female cancer survivors . Previous studies have indicated that website attributes, Internet usage patterns, and habits are different across genders . The differences in the findings of our review and those from the other reviews suggest that the effects of TBIs may also vary by gender.…”
Section: Discussioncontrasting
confidence: 49%
“…This finding was somewhat surprising as the surrogate seekers in the present study were younger than the self‐seekers, and they included a higher rate of males than females. According to previous research, younger individuals, especially males, tended to favor digital communication services over nondigital services . Research also reported that family members preferred health‐care professionals as sources of information .…”
Section: Discussionmentioning
confidence: 91%
“…Low rates of online health information seeking were reported among older adults, among people with low educational attainment, and in men compared to women. [18][19][20][21]. Regarding the use of eHealth tools among ethnic minorities, the data is inconclusive.…”
Section: The Role Of Sociodemographicsmentioning
confidence: 99%